Clientelism in the Public Sector : Why Public Service Reforms Fail and What to Do about It - Bold, Tessa (World Bank, Washington, DC, 2018)
In many developing countries (and beyond), public sector workers are not just simply implementers of policies designed by the politicians in charge of supervising them -- so called agents and principals, respectively. Public sector workers can have the power to influence whether politicians are elected, thereby influencing whether policies to improve service delivery are adopted and how they are implemented, if at all. This has implications for the quality of public services: if the main purpose of the relationship between politicians and public servants is not to deliver quality public services, but rather to share rents accruing from public office, then service delivery outcomes are likely to be poor. This paper reviews the consequences of such clientelism for improving service delivery, and examines efforts to break from this "bad" equilibrium, at the local and national levels.